Upward Pricing Pressure of Mergers Weakening Vertical Relationships - Gregor Langus; Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2015)
We modify the UPP test of Farrell and Shapiro (2010) to take into account the possibility that a merger weakens (or eliminates) a vertical supply relationship. After deriving a general effect of the merger, we provide an example of simple estimation strategy when only prices, costs and market shares are available as a snapshot.
Keywords: K21; L49; 330; UPP; supply relationship; merger effects